PRINCIPLES OF STATE FINANCIAL CONTROL OF UKRAINE IN THE CONDITIONS OF EUROPEAN INTEGRATION - Yuliya Pustovit; Viktor Timashov; Alina Berher (Baltic Journal of Economic Studies, 2018)
The purpose of the study is an improvement of principles of state financial control of Ukraine taking into account European advanced experience. The subject of the research is a comparative analysis of financial control principles and principles of state financial control of Ukraine with the international principles of financial control, envisaged at the international level, and the establishment of the expediency of their implementation in the national legislation in connection with the terms of European integration. The methodological background of the research is the combination of theoretical and scientific methods: analysis, synthesis and comparison, theoretical and logical generalization. The theoretical approaches are analysed according to the determination of conceptcategory of terms: “principle of financial control,” “principle of state financial control.” Existed principles of financial control, principles of state financial control of Ukraine, leading principles of financial control, what determined in Lima Declarations of Guidance on Auditing Precepts, general principles of supreme bodies of financial control activity that are envisaged in Declaration about general principles of supreme bodies of financial control activity of states-participants of CIS are investigated. Carrying out the analysis of financial control principles, principles of state financial control of Ukraine, and international principles of financial control, we reached a conclusion that basic principles (principles of legality, independence, objectivity, impartiality, publicity, neutrality) are already normatively envisaged. There is the part of international principles (principle of competence, publicity, efficiency, well-proven, observance of professional ethics, violation prevention, obligatory of responsibility offensive for the accomplished violations of financial discipline) that doesn’t have the normative consolidation in laws and regulations of Ukraine. International principles of financial control are partly marked in the scientific literature of Ukraine, but it not enough in order that they become leading ideas, the fundamental basis of the financial control system development of European standard in Ukraine. Conclusions. It is suggested to improve the statutory provision of state financial control: to manage further development of conceptual bases of the system of state financial control principles, their classification; in branch legislation, to specify principles of state financial control in accordance with their kinds; to complement the Law of Ukraine “On Basic Principles of State Financial Control Realization in Ukraine.” The list of realization principles of state financial control in Ukraine that will become one of the meaningful steps on the way of European integration of Ukraine to the European Union is envisaged.